Herpesvirus Infection Induces both Specific and Heterologous Antiviral Antibodies in Carp - Coll, Julio M. (Frontiers in Immunology, 2018)
IgM antibody diversity induced by viral infection in teleost fish sera remains largely unexplored despite several studies performed on their transcript counterparts in lymphoid organs. Here, IgM-binding to microarrays containing ~ 20000 human proteins was used to study sera from carp (Cyprinus carpio) populations having high titres of viral neutralization in vitro after surviving an experimental infection with cyprinid herpes virus 3 (CyHV-3). The range of diversity of the induced antibodies was unexpectedly high, showing CyHV-3 infection-dependent, non-specific IgM-binding activity of an ~20-fold wider variety than that found in sera from healthy carp (natural antibodies) with no anti-CyHV-3 neutralization titres. An inverse correlation between the IgM-binding levels in healthy versus infection-survivor/healthy ratios suggests that an infection-dependent feed back-like mechanism may control such clonal expansion. Surprisingly, among the infection-expanded levels, not only specific anti-frgIICyHV-3 and anti-CyHV-3 IgM-binding antibodies but also antibodies recognizing recombinant fragment epitopes from heterologous fish rhabdoviruses were detected in infection-survivor carp sera. Some alternative explanations for these findings in lower vertebrates are discussed.